Pengenalan Karakter Diri Melalui Konsep STIFIN untuk Melatih Kemampuan Literasi Numerasi Pemuda Desa Kerakas - Lathiifah, Iis Juniati; Agustine, Putri Cahyani; Hevitria, Hevitria (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
The success of a village is determined by its vast resources. Kerakas Village, located in Sungai Selan District, Central Bangka Regency, have village teenager who actively. However, there are many village teenager who are not yet information literate. There are very few young people who have good literacy and numeracy skills. This causes not many young people to aspire to progress. The activity aims to help village youth become literate for the future, starting with numeracy literacy. The activity was carried out on February 12, 2025 at the Kerakas Village office with material on self-character recognition through the STIFIN concept to support improving numeracy literacy skills. The socialization method is implemented with three activity steps, namely preparation, implementation and evaluation. The results of the activity showed that by using initial mapping, 25% of participants had an intuitive type of intelligence engine there was an increase in numeracy literacy skills seen from the way participants solved the problems given related to finance. The evaluation results showed that 85.15% of participants felt very satisfied with the activities provided.